Assessment Of Blue Led Light As A Novel Method For Enhancing Microbial Safety In Different Fruit Juices (Journal of Namibian Studies : History Politics Culture, 2023)
The antimicrobial activity of three fruit juices—orange, apple, and pomegranate—is assessed in this research by subjecting them to blue LED light therapy. To avoid heat-related effects, freshly made juice samples were exposed to blue LED light at 450 nm for different periods while being kept at 4°C. Total viable counts (TVC) and particular pathogens, such as Salmonella and Escherichia coli, were evaluated using microbial analysis. Longer exposure durations resulted in higher decreases in germ burdens, although the findings were significant across the board for all juice samples. In particular, the TVC in orange, apple, and pomegranate juices was reduced by 80.98%, 82.37%, and 81.78%, respectively, after 30 minutes of exposure. Additionally, all juices with the greatest exposure period had a 90% drop in E. coli and Salmonella levels.